2014
DOI: 10.1038/gt.2013.85
|View full text |Cite
|
Sign up to set email alerts
|

Leptin gene therapy attenuates neuronal damages evoked by amyloid-β and rescues memory deficits in APP/PS1 mice

Abstract: There is growing evidence that leptin is able to ameliorate Alzheimer's disease (AD)-like pathologies, including brain amyloid-β (Aβ) burden. In order to improve the therapeutic potential for AD, we generated a lentivirus vector expressing leptin protein in a self-inactivating HIV-1 vector (HIV-leptin), and delivered this by intra-cerebroventricular administration to APP/PS1 transgenic model of AD. Three months after intra-cerebroventricular administration of HIV-leptin, brain Aβ accumulation was reduced. By e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 62 publications
1
43
0
Order By: Relevance
“…Bath application of leptin reversed LTP suppression induced by acute perfusion of Aβ1-42 in hippocampal slices (Doherty et al, 2013). Leptin gene therapy rescued working memory in an APP/PS1 mouse model of AD in a T-maze task (Perez-Gonzalez et al, 2014). Leptin had beneficial effects on memory consolidation in a water maze task (Oomura et al, 2006) and in leptin-deficient rodents (Li et al, 2002); and leptin-treated TgCRND8 animals significantly outperformed saline-treated littermates in the novel object recognition test and fear conditioning test (Farr et al, 2006;Greco et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bath application of leptin reversed LTP suppression induced by acute perfusion of Aβ1-42 in hippocampal slices (Doherty et al, 2013). Leptin gene therapy rescued working memory in an APP/PS1 mouse model of AD in a T-maze task (Perez-Gonzalez et al, 2014). Leptin had beneficial effects on memory consolidation in a water maze task (Oomura et al, 2006) and in leptin-deficient rodents (Li et al, 2002); and leptin-treated TgCRND8 animals significantly outperformed saline-treated littermates in the novel object recognition test and fear conditioning test (Farr et al, 2006;Greco et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…PI3-k/Akt is important for protein synthesis (Karpova et al, 2006;Peltier et al, 2007), we suspect that enhancement of synthesis of synaptic proteins may be responsible for reversal of Aβ-induced deficit in L-LTP by leptin treatments. Additionally, leptin also facilitates the uptake of ApoE-bound Aβ and reduces the Aβ level and plaque deposition in an Alzheimer mouse model (TgCRND8) (Fewlass et al, 2004;Greco et al, 2010) and leptin gene therapy prevents the reduction of the number of dendrite spines in the APP/PS1 mouse model (Perez-Gonzalez et al, 2014). Leptin signaling desensitizes in obese patients and some AD patients (Bonda et al, 2014;Lee et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the treatment regimen was perfectly suited for PAS-leptin and suggests benefits in clinical settings. It is worth mentioning that not only LD patients should profit from PAS-leptin; several preclinical studies in mice have suggested that individuals suffering from type 1 and type 2 diabetes or neurodegenerative diseases may also benefit from optimised leptin analogues [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…The latter, highlights the anorexigenic leptin functions that are well described in the literature. However, mounting evidence also suggest other central actions of leptin in multiple sclerosis, amyotrophic lateral sclerosis, Alzheimer, that remain to be better understood [2325]. …”
Section: Leptin and Central Nervous Systemmentioning
confidence: 99%